2012 4th Electronic System-Integration Technology Conference 2012
DOI: 10.1109/estc.2012.6542177
|View full text |Cite
|
Sign up to set email alerts
|

Plasma dicing enables high accuracy self-alignment of thin silicon dies for 3D-device-integration

Abstract: Thin silicon chips with a thickness of 50 m are of light weight and are able to swim on droplets of fluids like for instance water. If the liquid shows a specific wetting behavior with respect to the underlying substrate then droplet and chip can move and self-align. Recent research work was carried out to determine the self-alignment accuracy of 50 m thin silicon dies on plasma programmed surfaces. The self-alignment process sequence for die assembly comprise the following steps: surface programming by CF4 pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…After successful self-alignment of the chips on the wafer substrate, IR microscopy analysis conducted on the samples revealed that the overall alignment accuracy was well below 3 μm and an accuracy in the range of just 1 μm was observed several times repeatedly [50]. Figure 16 exhibits the alignment accuracy graph of 7×7 mm 2 chips on a wafer substrate.…”
Section: Self-alignment Of Chipsmentioning
confidence: 99%
“…After successful self-alignment of the chips on the wafer substrate, IR microscopy analysis conducted on the samples revealed that the overall alignment accuracy was well below 3 μm and an accuracy in the range of just 1 μm was observed several times repeatedly [50]. Figure 16 exhibits the alignment accuracy graph of 7×7 mm 2 chips on a wafer substrate.…”
Section: Self-alignment Of Chipsmentioning
confidence: 99%